2022
DOI: 10.1111/cote.12654
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and application of ozone fading: Oxidative decolorisation of disperse dyes and waste‐dyed polyester fabrics

Abstract: As the most common synthetic fibre, polyester has consistently been in high demand and usage, but its recycling has always been a problem for the textile industry. The decolorisation of dyed polyester is the key to expanding its recycling use, and there is no rapid, effective and simple decolorisation method. In this study, ozone was used to decolorise dispersed dyes developed for polyester. Ozone was effective in decolorising CI Disperse Orange 30 and CI Disperse Blue 60, and the process was extended to the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In the case of plasma, Peran and Razic [ 38 ] and Ayesh et al [ 39 ] stated that the effect of the plasma is dependent of the conditions under which the fiber is exposed in the treatment. Similarly, Lou et al [ 40 ] demonstrated that ozone affects the surface morphology of polyester fibers. In this study, the ability of the polyester fiber treated with plasma and ozone to adhere to the biopolymer was very similar, and the effect was related to the particle size.…”
Section: Resultsmentioning
confidence: 94%
“…In the case of plasma, Peran and Razic [ 38 ] and Ayesh et al [ 39 ] stated that the effect of the plasma is dependent of the conditions under which the fiber is exposed in the treatment. Similarly, Lou et al [ 40 ] demonstrated that ozone affects the surface morphology of polyester fibers. In this study, the ability of the polyester fiber treated with plasma and ozone to adhere to the biopolymer was very similar, and the effect was related to the particle size.…”
Section: Resultsmentioning
confidence: 94%
“…The disappearance of these peaks, along with the absence of the C-H peak after the ozonation process, provides supporting evidence for the effectiveness of ozonation. Ozone plays a pivotal role in the degradation of disperse dyestuffs [ 44 ]. The improvement in test success post-ozonation is further substantiated by the elimination of dyestuff groups that may contribute to combustion.…”
Section: Resultsmentioning
confidence: 99%
“…Ozonated polyester fabric also showed a crystalline ratio of 37.87%. The crystallinity of the dyed PET fabric also decreased from 41.41% to 37.87% [38]. When the figure is examined, it is seen that the ozone gas flow rate increased, no significant change was observed in the hydrophilicity values of the samples, but the ozone treatment time is effective.…”
Section: Hydrophilicitymentioning
confidence: 93%
“…These groups increase the hydrophilicity of the samples. In addition, Lou et al [38] conducted XRD analyses of raw and ozonated polyester fabrics after dyeing. According to the study, untreated raw PET fabric showed a crystalline ratio of 41.41%.…”
Section: Hydrophilicitymentioning
confidence: 99%